Kepuasan Kerja dan Dampaknya terhadap Unjuk Kerja Guru di Gugus Pantai Kartini UPT Dinas Pendidikan Kecamatan Mojolaban (Tinjauan Aspek Keteladanan Pimpinan dan Ketrampilan Pemanfaatan Media) - Sugiati, Emi (Jurnal VARIDIKA, 2013)
This research aims to describe : 1) the contribution of leader exemplary and learning media model through indirect satisfied concerning the characteristic of the teacher performance, 2) The contribution of leader exemplary and the satisfied learning media model, 3) the satisfied of the teacher performance. The result is expected to gave information to the headmaster, so its can become reconciliation to increase the school work and for the teacher they can get a feet-back about the increase of the work. This quantitative research has used inquiry method that proved valid and reliable and documentations method a means of principal data collecting, and to test direct and indirect contribution between keteladanan leadership, study media, satisfaction and performance teacher at coast cluster Kartini UPT district Mojolaban education official use stripe analysis method (path Analysis). population in these watchfulness teachers coast cluster Pantai Kartini UPT district education official Mojolaban as much as 141 person, with sample as much as 106 person. The result show that : 1) The leader exemplary and learning media give direct contribution for the teacher performance, 2) The leader exemplary and learning media give direct significant to the satisfied, 3) The satisfied give direct contribution and significant for the performance of the teacher in coast cluster Pantai Kartini Education Official UPTD Mojolaban sub district.